2018
DOI: 10.1016/j.athoracsur.2017.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Team Behaviors in Surgery: A Qualitative Study to Inform Teamwork Interventions

Abstract: BackgroundSurgical excellence demands teamwork. Poor team behaviors negatively affect team performance and are associated with adverse events and worse outcomes. Interventions to improve surgical teamwork focusing on frontline team members’ nontechnical skills have proliferated but shown mixed results. Literature on teamwork in organizations suggests that team behaviors are also contingent on psychosocial, cultural, and organizational factors. This study examined factors influencing surgical team behaviors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 25 publications
(40 reference statements)
1
25
0
1
Order By: Relevance
“…For instance, multiple studies have evaluated factors that influence surgical team behaviors and found that many OR team members may hold dissimilar beliefs and goals related to which behaviors enhance teamwork in the OR. [25][26][27] In addition, others have suggested that QI and awareness campaigns are vital to changing OR behavior as it relates to adherence to infection control practices in the OR. 26,28 Moreover, despite differences in team dynamics, studies indicate that positive behavior change in the OR is possible.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, multiple studies have evaluated factors that influence surgical team behaviors and found that many OR team members may hold dissimilar beliefs and goals related to which behaviors enhance teamwork in the OR. [25][26][27] In addition, others have suggested that QI and awareness campaigns are vital to changing OR behavior as it relates to adherence to infection control practices in the OR. 26,28 Moreover, despite differences in team dynamics, studies indicate that positive behavior change in the OR is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we are developing a greater appreciation of the wide range of contextual factors that influence interprofessional interactions, and the resulting variability in the nature of these interactions. Research in various clinical contexts, including intensive care, emergency, and surgery, show how professional and patient-related characteristics, technology, organizational culture, structures and processes, and policy priorities all impact on the nature and conditions of interprofessional practice (Aveling et al, 2018;Broom et al, 2015;Liberati, 2017;Lindberg et al, 2017;Xyrichis et al, 2017). For example, in a study in the intensive care unit, staff seniority and urgency of work influenced jurisdictional boundaries and professional interactions (Xyrichis et al, 2017).…”
Section: Sociological Insightsmentioning
confidence: 99%
“…For example, in a study in the intensive care unit, staff seniority and urgency of work influenced jurisdictional boundaries and professional interactions (Xyrichis et al, 2017). In the operating room setting, a range of factors including technical demands of the case, patient acuity, trainee turnover and nurse scheduling influenced interprofessional interactions (Aveling et al, 2018). At a policy level, we have seen how a policy about antimicrobial resistance impacted on professional negotiations amongst pharmacists and physicians in hospital settings (Broom et al, 2015).…”
Section: Sociological Insightsmentioning
confidence: 99%
“…Professional training shortfalls were highlighted, and it is important to consider the need for greater interaction with the Universities, and training and regulatory organizations of the mid-level and higher-level professionals involved. Technical competence is strongly valued in building trusting relationships for teamwork [ 29 ]. At the same time, issues such as teamwork, coordination of services and communication are still insufficiently incorporated in the curricula [ 21 – 23 ].…”
Section: Discussionmentioning
confidence: 99%